Evaluating Serum Calprotectin and Serum Oncostatin M Levels as Diagnostic Markers in Crohn's Disease and Ulcerative Colitis Iraqi Patients. Research - Yahya G. Karwi; Inam S. Arif; Shaymaa A. Abdulameer (College of Pharmacy / Mustansiriyah University, 2024)
Abstract Introduction: Inflammatory bowel disease (IBD), comprising Crohn's disease (CD) and ulcerative colitis (UC), presents as chronic gastrointestinal inflammation. Timely diagnosis and effective monitoring are crucial for better outcomes. This study aims to explore serum calprotectin and oncostatin M as potential biomarkers for diagnosing and monitoring CD and UC. Calprotectin, released during inflammation, and oncostatin M, an immune-response cytokine, have shown promise, but their precise role in IBD remains unclear. Methodology: Using a cross-sectional observational design, the study included 93 IBD patients on biological treatment (50 CD, 43 UC) at Baghdad Teaching Hospital. Demographic data and disease characteristics were collected via interviews, and blood samples were analyzed using specific ELISA kits for calprotectin and oncostatin M levels. Results: The results demonstrated significantly elevated serum levels of both biomarkers in IBD patients, increasing with disease activity. Significant distinctions were observed among different disease statuses in UC and CD patients. Conclusion: These findings suggest that serum calprotectin and oncostatin M have potential as practical and non-invasive biomarkers for diagnosing and monitoring IBD. However, further research is required to validate their clinical utility and optimize IBD management.